Occurrence of Yersinia spp. in food in Brazil - Falcao, D. P. (Elsevier B.V., 1991)
Over the past 9 years, 468 bacterial strains isolated from raw and pasteurized milk, beef and pork, bovine and chicken liver, chicken heart, gizzards and lung sausage, hamburger, cheese and lettuce in different regions of the State of Sao Paulo and in the city of Rio de Janeiro were received by the Reference Laboratory for Yersinia in Brazil. All were confirmed to be Yersinia spp. The 468 Yersinia isolates were grouped as 184 strains because some of the bacteria isolated from the same food sample belonged to the same species, and were considered to be a single strain. The Yersinia food strains were classified as Y. enterocolitica (46), Y. intermedia (67), Y. frederiksenii (20), Y. kristensenii (8) and 43 of them were biochemically atypical. Pathogenic types were not detected.
Keywords: Brazil; Food contamination; Meat; Milk; Nonhuman; Priority journal; Yersinia; Bacterial Typing Techniques; Food Microbiology